La défense nationale comme justification de l’action politique. Le prétorianisme au Venezuela 1958-2022 - Andrés Zambrano (IdeAs)
The evolution of the doctrine of national defense in the Venezuelan Armed Forces has been reconstructed, from 1958 to 2022, based on the examination of works of political history, testimonies of those involved and State publications : Constitution, laws and decrees. The objective is to present the evolution of national defense as an institution that serves as a normative orientation for the actors of the Venezuelan political order, leading to a praetorian practice at the beginning of the 21st century. The study makes three contributions to the understanding of contemporary Venezuela : first, it highlights praetorianism as an institution of the Venezuelan political system. Second, it shows that praetorianism is predominant or subordinate in relation to other institutions depending on the historical moment studied. Finally, the changes in the doctrine of national defense show that the return of military control over the State does not only respond to pragmatic interests such as power and economic privileges ; it must also consider political ideals as a group, highlighting the importance of the normative dimension in collective life.